Українське початкове шкільництво на Волині у 1921 – 1926 роках - Крамар, Юрій Вікторович; Kramar, Yurii V. (Волинський державний університет імені Лесі Українки, 1997)
Проаналізовано стан українського початкового шкільництва на Волині у 1921 – 1926 роках. Досліджено політику польської влади щодо українських шкіл та нормативно-правові засади його організації в Другій Речі Посполитій. Визначено засоби ліквідації українських шкіл.

The state of Ukrainian elementary schooling in Volyn in 1921 - 1926 years has been analyzed. The policy of the Polish authorities concerning the Ukrainian schools and the legal and regulatory framework of its organization in the Second Republic of Poland have been explored. The means of liquidation of Ukrainian schools are determined.
Ukrainian primary school in Volyn in 1921-1926
Keywords: Волинь; українське шкільництво; шкільний плебісцит; двомовні школи; початкова школа; Volyn; Ukrainian schooling; school plebiscite; bilingual schools; Elementary School